Identifikasi Unjuk Kerja Mesin 4 Langkah Variasi Busi dan Koil Pengapian - Muhammad, Rouf; Ardika, Rizki Dwi; Soumi, Andi Ibrahim; Pramanda, Wibi; Safi'i, Muhamad (Universitas Muria Kudus, 2024)
The most critical component of a motorcycle's combustion process is the spark plug, which fires sparks for the ignition system. In this research, the performance of several spark plug electrode gap diameters and materials was varied to detect how much they affected engine performance, fuel consumption, and emissions. Engine testing was conducted on a 110-cc four-stroke engine. Nickel material spark plugs with a gap dimension of 0.9 mm, platinum material spark plugs with a gap dimension of 0.8 mm, iridium material spark plugs with a gap dimension of 0.7 mm, and two types of ignition coils. The test findings indicated that there is a spark plug with an appropriate gap for engine performance in the form of torque and power in the B2 configuration, which has a gap of 0.8 mm. Increasing the spark plug gap produces a loss in engine performance, but it also increases it. There is an optimal point of fuel consumption in configuration B2, where raising the spark plug gap decreases fuel consumption while increasing the spark plug gap increases fuel consumption. Exhaust emissions likewise experience an optimal point in configuration B2, when exhaust emissions rise as long as the spark plug gap is increased once more, HC and CO levels decrease with an increasing spark plug gap. To examine the study on the impact of spark plugs with electrode gaps and ignition coils on engine performance, fuel consumption, and emissions. This can provide insight into a reference technique for using spark plugs and ignition coils.